The role of philosophy in the formation of the ancient Turkic state policy of Kazakhstan as an independent sovereign state. (Journal of Oriental Studies, 2016)
This article discusses current research problems and the formation of the ancient Turkic statehood analizirutsya its role in the formation of the Kazakh independent statehood.
Keywords: Gunsky state; Turkic khaganate; Kypchaksky society; Turkic world; independence; gosurdarstvo; tyurkologiya; national tradition